Preoperative Determination of Isocitrate Dehydrogenase Mutation in Gliomas Using Spectral Editing MRS: A Prospective Study. Issue 2 (17th September 2020) - Nguyen, Thanh B.; Melkus, Gerd; Taccone, Michael; Moldovan, Ioana D.; Ghinda, Diana; Gotfrit, Ryan; Torres, Carlos H.; Zakhari, Nader; Chakraborty, Santanu; Woulfe, John; Jansen, Gerard; McInnes, Matthew DF.; et al.
Abstract : Background: The edited magnetic resonance spectroscopy (MRS) technique has not yet been formally evaluated for the in vivo detection of 2‐hydroxyglutarate (2‐HG) in patients with gliomas of various grades. Purpose: To evaluate the diagnostic accuracy of edited MRS in the preoperative identification of the isocitrate dehydrogenase (IDH) mutation status in patients with gliomas. Study Type: Prospective. Population: Fifty‐eight subjects (31 glioblastomas, 27 grade II and III gliomas). Field Strength/Sequence: Mescher–Garwood (MEGA)‐PRESS and routine clinical brain tumor MR sequences were used at 3T. Assessment: Data were analyzed using an advanced method for accurate, robust, and efficient spectral fitting (AMARES) from jMRUI software. The amplitudes of the 2‐HG, N‐acetyl‐aspartate (NAA), choline (Cho), and creatine/phosphocreatine (Cr) resonances were calculated with their associated Cramer–Rao lower bound (CRLB). The IDH1 R132H mutation status was assessed by immunohistochemistry for all patients. Patients with grades II and III gliomas with negative immunohistochemistry underwent DNA sequencing to further interrogate IDH mutation status. Statistical Test: The differences in 2‐HG amplitudes, 2‐HG/NAA, 2‐HG/Cho, and 2‐HG/Cr between IDH‐mutant and IDH‐wildtype gliomas were assessed using Mann–Whitney U ‐tests. Receiver operating characteristic curve analysis was performed to evaluate the diagnostic accuracy of each parameter. Results: The 2‐HG amplitudes, 2‐HG/NAA, and 2‐HG/Cho were higher for IDH‐mutant gliomas than IDH‐wildtype gliomas ( P < 0.007). Using a CRLB threshold <30%, a 2‐HG cutoff greater than 0 had a sensitivity of 80% (95% confidence interval [CI]: 52–96%) and a specificity of 81% (95% CI: 54–96%) in identifying IDH‐mutant gliomas. In the subset of patients with grades II and III gliomas, the sensitivity was 80% (95% CI: 52–96%) and specificity was 100% (95% CI: 40–100%). Among 2‐HG ratios, the highest AUC for the identification of IDH mutant status was achieved using the 2‐HG/NAA (AUC = 0.8, 95% CI 0.67–.89). Data Conclusion: Preoperative edited MRS appears to be able to help identify IDH‐mutant gliomas with high specificity. Level of Evidence 1 Technical Efficacy Stage 2 J. MAGN. RESON. IMAGING 2021;53:416–426.